2022
DOI: 10.1007/s12011-022-03298-0
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Effects of Silver Nanoparticles and Spirulina Extract on Experimentally Induced Prostatic Cancer in Rats

Abstract: Prostate cancer (PCa) is the most diagnosed cancer in 112 countries and the second leading cause of death in men in 48 countries. We studied the outstanding agents silver nanoparticles (AgNPs) and Spirulina algae (Sp) for the management of PCa once as monotherapy or last as a combination. PCa in rats was induced using bicalutamide (Casodex®) and testosterone, followed by (7, 12-dimethylbenz[a]anthracene). Then, testosterone was injected s.c. for 3 months. Rats were divided into six groups, with 12 rats in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…SEM analysis employs an electron microscope to determine the presence of silver nanoparticles [24] . The spherical shape of AgNP with homogeneous shape and size is depicted in the SEM analysis [25] . SEM was used to determine the morphological characteristics of silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM analysis employs an electron microscope to determine the presence of silver nanoparticles [24] . The spherical shape of AgNP with homogeneous shape and size is depicted in the SEM analysis [25] . SEM was used to determine the morphological characteristics of silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…[24] The spherical shape of AgNP with homogeneous shape and size is depicted in the SEM analysis. [25] SEM was used to determine the morphological characteristics of silver nanoparticles. The critical analysis revealed that the silver nanoparticles of S. platensis were faintly clustered, mostly circular, and found throughout the region where they formed.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers used biogenic Ag@NP which displayed potent toxic effects against both cancer cell lines and pathogens, and also exhibited antioxidant activity (Wei et al, 2021). Recently Ag@NP were also tested with spirulina on rats to treat prostate cancer, and it was found that a class of rats showed good result in the context of treatment with stability in hormone imbalance (El-Magid et al, 2022).…”
Section: General Publication Trendmentioning
confidence: 99%